Exact stochastic simulation of a calcium microdomain reveals the impact of Ca2+ fluctuations on IP3R gating - Wieder, Nicolas Wolfgang; Fink, Rainer; Wegner, Frederic von (Biophysical journal, 2015)
In this study, we numerically analyzed the nonlinear Ca2+-dependent gating dynamics of a single, nonconducting inositol 1,4,5-trisphosphate receptor (IP3R) channel, using an exact and fully stochastic simulation algorithm that includes channel gating, Ca2+ buffering, and Ca2+ diffusion. The IP3R is a ubiquitous intracellular Ca2+ release channel that plays an important role in the formation of complex spatiotemporal Ca2+ signals such as waves and oscillations. Dynamic subfemtoliter Ca2+ microdomains reveal low copy numbers of Ca2+ ions, buffer molecules, and IP3Rs, and stochastic fluctuations arising from molecular interactions and diffusion do not average out. In contrast to models treating calcium dynamics deterministically, the stochastic approach accounts for this molecular noise. We varied Ca2+ diffusion coefficients and buffer reaction rates to tune the autocorrelation properties of Ca2+ noise and found a distinct relation between the autocorrelation time τac, the mean channel open and close times, and the resulting IP3R open probability PO. We observed an increased PO for shorter noise autocorrelation times, caused by increasing channel open times and decreasing close times. In a pure diffusion model the effects become apparent at elevated calcium concentrations, e.g., at [Ca2+] = 25 μM, τac = 0.082 ms, the IP3R open probability increased by ≈20% and mean open times increased by ≈4 ms, compared to a zero noise model. We identified the inactivating Ca2+ binding site of IP3R subunits as the primarily noise-susceptible element of the De Young and Keizer model. Short Ca2+ noise autocorrelation times decrease the probability of Ca2+ association and consequently increase IP3R activity. These results suggest a functional role of local calcium noise properties on calcium-regulated target molecules such as the ubiquitous IP3R. This finding may stimulate novel experimental approaches analyzing the role of calcium noise properties on microdomain behavior.
Gesehen am 01.07.2020
Im Titel ist "2+" in Ca2+ hochgestellt
Im Titel ist "3" in IP3R tiefgestellt